Force-producing ADP state of myosin bound to actin - Wulf, Sarah Elise Freyja; Ropars, Virginie; Fujita-Becker, Setsuko; Oster, Marco; Hofhaus, Götz; Trabuco, Leonardo G.; Pylypenko, Olena; Sweeney, H. Lee; Houdusse, Anne M.; Schröder, Rasmus R. (Proceedings of the National Academy of Sciences of the United States of America, 2016)
Molecular motors produce force when they interact with their cellular tracks. For myosin motors, the primary force-generating state has MgADP tightly bound, whereas myosin is strongly bound to actin. We have generated an 8-Å cryoEM reconstruction of this state for myosin V and used molecular dynamics flexed fitting for model building. We compare this state to the subsequent state on actin (Rigor). The ADP-bound structure reveals that the actin-binding cleft is closed, even though MgADP is tightly bound. This state is accomplished by a previously unseen conformation of the β-sheet underlying the nucleotide pocket. The transition from the force-generating ADP state to Rigor requires a 9.5° rotation of the myosin lever arm, coupled to a β-sheet rearrangement. Thus, the structure reveals the detailed rearrangements underlying myosin force generation as well as the basis of strain-dependent ADP release that is essential for processive myosins, such as myosin V.
Gesehen am 18.02.2020